2000
DOI: 10.1046/j.1365-2249.2000.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with anti-CD86 costimulatory molecule prevents the autoimmune lesions in murine Sjögren’s syndrome (SS) through up-regulated Th2 response

Abstract: SUMMARYIntraperitoneal administration with anti-CD86 (B7.2) MoAb into the murine model for primary SS in NFS/sld mutant mice resulted in dramatically inhibitory effects on the development of autoimmune lesions, while no signi®cant effects were observed when the mice were administered with anti-CD80 (B7.1) MoAb. We found that spleen cells in the murine SS model treated with anti-CD86 MoAb showed a signi®cant impairment of autoantigen-speci®c T cell proliferation. T cell activation markers (CD44 high , CD45RB lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In contrast, once activated ex vivo, BDC2.5 cells could efficiently transfer diabetes in B7-2KO mice. These observations provide further credence to the notion that B7-2 plays a significant role during the initiation of autoreactive T cell responses (18,38,39) and is dispensable during the later (effector) phase of the immune response. Accordingly, late B7-2 blockade in NOD (10 wk of age or older) is ineffective in controlling diabetes (13).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In contrast, once activated ex vivo, BDC2.5 cells could efficiently transfer diabetes in B7-2KO mice. These observations provide further credence to the notion that B7-2 plays a significant role during the initiation of autoreactive T cell responses (18,38,39) and is dispensable during the later (effector) phase of the immune response. Accordingly, late B7-2 blockade in NOD (10 wk of age or older) is ineffective in controlling diabetes (13).…”
Section: Discussionsupporting
confidence: 71%
“…It is likely that local cellular interactions and the cytokine/chemokine microenvironment may play a role in this tissue specific up-regulation of B7-1. Moreover, B7-1 has been shown to play an important role in the effector phase of immune response (9,45), whereas B7-2 regulates the initiation phase (5,38,46,47). Furthermore, despite the presence of enhanced B7-1 signals in the spleen, there is an absence of pathogenic islet reactive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated whether ED administration of CD4 effectively inhibits autoimmune pathology in the lacrimal glands of a mouse model of SS (12). We have previously reported that anti-CD86 mAb treatment improved the autoimmune pathology in both the lacrimal and the salivary glands of mice with SS (30). We used an antibody because the specific binding ability of a mAb against the target molecule allows the establishment of a molecule-specific therapeutic strategy with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, blocking B7.1 activity in SJL mice inhibited the induction of pathogenic Th1 response and abrogated susceptibility to experimental autoimmune encephalomyelitis, while blocking B7.2 functions inhibited Th2 responses and led to disease exacerbation (17,18). In other models of murine autoimmune disease, such as diabetes in NOD mice (19) and Sjogren's syndrome in NFS/sld mice (20), blocking B7.2, in contrast, prevented disease development. In the murine model of mercury-induced autoimmunity where both Th1 and Th2 responses are involved, B7.1 and B7.2 were found to regulate different manifestations of the autoimmune syndrome, and absence of either one did not completely protect from disease (21).…”
mentioning
confidence: 99%